The Prevalence of Imperial Ideologies in Joseph Conrad’s Heart of Darkness (Journal of the College of Basic Education, 2022)
Heart of Darkness is a novel written in the 19th century by Joseph Conrad. It recounts the details of Charlie Marlowe’s expedition into the African prairie tracing the European mission there. In his trip, Marlowe registers his observations of how the white Europeans through coercion and violence are taking advantage of the black Africans, eventually making them into lifelong slaves. The novel could be read as a disparaging work for the white European imperial and dehumanizing practices against black Africans. However, the current paper argues that Conrad in his novel has contributed to the promotion and perpetuation of the Western’s established and ideologically propagated stereotypes and images of black Africans. It is worth mentioning to note that throughout the novel, black African continue to be represented as inferiors, savages, and primitive who deserve to be colonized and exploited. The way Conrad depicts black people in the novel corresponds closely with the official European attitude and propagated European imperial ideologies towards Africans at the time. Therefore, analyzing the novel from “an imperial and ideological perspectives will make us able to locate the novel in the complex system of power relations and cultural representations which form the discourse of colonialism,” (Branningan: 153, 1998).